2010
DOI: 10.1111/j.1469-8749.2009.03525.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gross motor capacity and daily‐life mobility in children with cerebral palsy

Abstract: AIM The aim of this study was to examine the relationship between gross motor capacity and daily-life mobility in children with cerebral palsy (CP) and to explore the moderation of this relationship by the severity of CP.METHOD Cross-sectional analysis in a cohort study with a clinic-based sample of children with CP (n=116; 76 males, 40 females; mean age 6y 3mo, SD 12mo, range 4y 8mo-7y 7mo) was performed. Gross motor capacity was assessed by the Gross Motor Function Measure (GMFM-66). Daily-life mobility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 26 publications
(47 reference statements)
2
78
2
3
Order By: Relevance
“…20 Holsbeeke et al reported that the correlations between motor capacity, motor capability, and motor performance were high, between 0.84 and 0.92, and significant (P <0.001) in children with CP aged 30 months on average. However, when comparing children with the same level of motor capacity or capability, large ranges at the level of motor performance were found.…”
Section: Discussionmentioning
confidence: 99%
“…20 Holsbeeke et al reported that the correlations between motor capacity, motor capability, and motor performance were high, between 0.84 and 0.92, and significant (P <0.001) in children with CP aged 30 months on average. However, when comparing children with the same level of motor capacity or capability, large ranges at the level of motor performance were found.…”
Section: Discussionmentioning
confidence: 99%
“…Ostensjo et al 32 reported a strong relation between GMFM-66 and the Pediatric Evaluation of Disability Inventory functional skills. Similarly, Smits et al 33 documented that the GMFM-66 scores explained 90% and 84%, respectively, of the variance of Pediatric Evaluation of Disability Inventory functional skills and caregiver assistance scales in 116 children with CP across all GMFCS levels. The mediation analysis presented here suggests that for ambulatory children the relation between activity capacity (what they do in a structured setting) and day-to-day participation is mediated largely through activity performance (what a child actually does in day-to-day life).…”
Section: Discussionmentioning
confidence: 87%
“…They also found that pain caused problems with sleep. When Tervo et al 4 interviewed the parents of 77 children aged 3 to 17 years, they found similar results. Sixty-one percent reported that their child had pain in the past week and 33% reported that the pain interfered with normal activities including mobility, self-care, and participation in physical education.…”
mentioning
confidence: 78%